Computer communications and networking technologies - Gallo, Michael A. Hancock, Bill.; Hancock, William M. ([S.l.] : Course Technology, 2012)
Many students in computer science and MIS use networking technologies when working on projects but are not responsible for building or designing networks. This book addresses the needs of those students. The authors provide students with an overview of networking technology without the mathematical rigor of textbooks written for networking engineers. Through his teaching experience, Michael Gallo has found that students are often needlessly overwhelmed by the more complex topics intended for network engineering students when all they really need is an understanding of how networks operate. This approach has proven to be successful in class tests. Rather than focus on one technology, the text provides an overview of several technologies, such as Ethernet, FDDI, ATM, and the Internet. The authors compare and contrast these technologies so the students will be able to apply this knowledge to a variety of situations. This approach prepares students for the different networks they may encounter.
Keywords: a